PEMBINAAN ANAK-ANAK PANTI ASUHAN PUTRI AISYIYAH BUKITTINGGI DENGAN KETERAMPILAN KREASI KERAJINAN ANYAMAN MELALUI PKM - Zubaidah A; Erwin Erwin; Nessya Fitriyona; Zubaidah Zubaidah (Jurusan Seni Rupa, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2019)
In the current era of globalization, a strategy for enhancing and developing Human Resources (HR) is needed. HR development is carried out to form quality personal through skills, work ability, and work loyalty to an institution, foundation or organization. No exception to the HR of the Children in the Orphanage. One effort that can be done is to help orphanage children to develop skills in the field of woven crafts with various types of materials and techniques for products of objects of wear and art. This woven skills training is packaged in the Community Partnership Program (PKM) which is very useful for orphanage children as a provision for them to become entrepreneurs later, if they are no longer the responsibility of the Foundation. To achieve the target as expected, this activity is carried out using lecture, presentation, question and answer, and assignment methods, so that each participant produces woven products / crafts that are of artistic value and use value as well as selling value.